2019
DOI: 10.1007/s00436-018-06195-5
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular characterization of the Taenia solium Tso31 antigen and homologous of other Taenia species from Peru

Abstract: Several studies have been performed to determine specific antigens for the diagnosis of tapeworms. One of these antigens is Tso31, which is used to differentiate Taenia solium and Taenia saginata in human feces. The aim of the present work was the molecular characterization of this protein in different tapeworm specimens collected in Peru, T. omisa (n = 6), T. hydatigena (n = 7), T. taeniaeformis (n = 4), T. pisiformes (n = 1), T. multiceps (n=7) and T. solium (n = 10). Total DNA was extracted from each proglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Tso31 gene is one of the most promising antigens to differentiate T.solium from T saginata. Since this gene is presented in T.solium but not in T.saginata, it was recommended for differential diagnosis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Tso31 gene is one of the most promising antigens to differentiate T.solium from T saginata. Since this gene is presented in T.solium but not in T.saginata, it was recommended for differential diagnosis (14).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed the amplification of a single 234-bp fragment only in the samples with T. solium DNA. However, Vargas-Calla et al (2019) evaluated whether the Tso31 gene was conserved in other Taenia species and found that PCR of it was negative in DNA from T. omisa, T. hydatigena, T. pisiformis , and T. taeniaeformis but was positive in T. multiceps ; the authors suggested that the Tso31 gene sequence is not exclusive to T. solium (13). Considering the above, it is important to continue evaluating the possible cross-reactions of this test with other, related parasites.…”
Section: Discussionmentioning
confidence: 99%